20-Hydroxyecdysone promotes release of GBP-binding protein from oenocytoids to suppress hemocytic encapsulation. (January 2018) - Zhuo, Xiao-Rong; Chen, Lei; Wang, Gui-Jie; Liu, Xu-Sheng; Wang, Yu-Feng; Liu, Ke; Yu, Xiao-Qiang; Wang, Jia-Lin
Abstract: Growth-blocking peptide (GBP) is an insect cytokine that stimulates plasmatocyte adhesion, thereby playing a critical role in encapsulation reaction. It has been previously demonstrated that GBP-binding protein (GBPB) is released upon oenocytoid lysis in response to GBP and is responsible for subsequent clearance of GBP from hemolymph. However, current knowledge about GBPB is limited and the mechanism by which insects increase GBPB levels to inactivate GBP remains largely unexplored. Here, we have identified one GBP precursor ( HaGBP precursor ) gene and two GBPB (namely HaGBPB1 and HaGBPB2 ) genes from the cotton bollworm, Helicoverpa armigera . The HaGBP precursor was found to be predominantly expressed in fat body, whereas HaGBPB1 and HaGBPB2 were mainly expressed in hemocytes. Immunological analyses indicated that both HaGBPB1 and HaGBPB2 are released from hemocytes into the plasma during the wandering stage. Additionally, 20-hydroxyecdysone (20E) treatment or bead challenge could promote the release of HaGBPB1 and HaGBPB2 at least partly from oenocytoids into the plasma. Furthermore, we demonstrate that the N-terminus of HaGBPB1 is responsible for binding to HaGBP and suppresses HaGBP-induced plasmatocyte spreading and encapsulation. Overall, this study helps to enrich our understanding of the molecular mechanism underlying 20E mediated regulation of plasmatocyte adhesion and encapsulation via GBP-GBPB interaction. Graphical abstract: Highlights: HaGBPB1 and HaGBPB2 are predominantly expressed in hemocytes. Release of HaGBPB1 and HaGBPB2 from hemocytes into plasma during wandering stage. 20E treatment or bead challenge can promote the release of HaGBPB from oenocytoids. HaGBPB1 binds to HaGBP through the N terminus and suppresses plasmatocyte spreading.